If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3*x+6/3 = x+2
pi-(sin(x))^(pi/2)
2*(1/3)-4 = 0
x-((1/3)*x)-4 = 1/2
b/3 > -4
| 4n+2n=12 | | 3=p+3-1 | | 13b-9=4b-63 | | -18n-30n=-18-10n | | 4=2x-3y | | -17=6b-7+8 | | 5x+2x-14=28 | | 2(x+2)=x-7 | | 1/3*2-4 | | -10=8b+8-5b | | 6+4n+5=-13 | | 1+4n+5=2 | | b/3-4 | | 18n-30n=-18-10n | | 1/3x0 | | 6x+5x-4x-5=23 | | 10=k+2-2k | | 3x+2(x-5)=c+6 | | 9=2n+n | | 2(x-4)+x=4x+5 | | n-3+8=4 | | -7n+7-7=21 | | -7x-3x=0 | | 15=-n+6n | | 7x+24=x+48 | | 6b-7b=4 | | 3x/0 | | 24x^2-44x-74=0 | | 7x/14=10-2x | | 14.5/4 | | x^4+5x^3+12x^2+16x+8=0 | | (s^3+4s^2+6s+4)=0 |